El control interno y su relación con la NIC 2 Aplicable en la unidad de control de activos de la Universidad Técnica Estatal de Quevedo, año 2012. - Coello Albán, Jennifer Nataly (2012)
This research was conducted at the State Technical University of Quevedo, in order to establish the relationship of internal control with IAS 2 unit to improve its assets. It was conducted based on methodologies such as inductive, descriptive and analytical to develop the research topic and reach the expected results. As part of asset control, financial management of the institution makes the procurement plan based on the availability of the budget assigned to the Central Government. Once done this analysis, it is sent through the Department of Public Procurement acquisitions of the institution through the different processes stable Organic Law of the National Public Procurement System. The merchandise arrives at the institution receiving the respective proof of delivery receipt, the same as is done by the control unit active, and verification prior approval by the Head of cellar. The inventory valuation method that performs the State Technical University Quevedo does not meet the provisions are stipulated in IAS 2, which shows a low level of operating efficiency and adequate distribution of the costs attributable to inventory. Pursuant to the questionnaires used to assess the internal control used to manage inventory at the State Technical University of Quevedo a 97.50% Confidence Level High and corresponding risk level of 2.50% was obtained representing low; these percentages correspond to the two findings identified during the assessment; these results were because specifically no written instructions as a guide for employees who perform physical inventories, on the other hand are prepared, no inventory records or other data is periodically analyzed to determine the rotation of existence, if they are excess or obsolete.